O passado presente em tela : uma leitura da fundamentação do conhecimento histórico nas experiências fílmicas da atual sociedade em rede - Sousa, Pollyana Iris Lima de (2016)
The research from which this work is an outcome was only possible to be done due to the opening that has occured in the historiographical field, enabling the emergence of new debates that approach history from an epistemological focus. We seek, within this context, to learn the relationship between cinema and history. In order to do so, another relationship guides our analysis, the one between the present and the past. We know that one of the main elements of history is time and our work acts on the interest of understanding the human being in time and space. Thisnotion of change and separation allows us to consider one event as historical or not. We want to understand this temporal relationship from the movies. We use in our work the expanded theory of cinema shown by Philippe-Alain Michaud, in which the movie isnot considered the equivalent of the public screening, but rather it is interpreted as a way of thinking the images through space-time parameters. This drifts away from the traditional perspective of evaluating the movies by changing the focus from the production to analysing its audience. Therefore, it is the historically located audience that gives sense to the viewed images and, in light of this, the way of thinking the images changes according to the observer’s time and space. The movie comes away fromthe technical details that support it and becomes independent. The audience is no more only a receptor of the projected images and becomes an important part of the process of the construction of the message that makes sense to them. We consider that it isthe audicente and its notion of temporality that givens the historical nature to the event represented on the images. Taking this theory as a guide, we will seek to understand how the Middle Ages represented in the movies can be learned by the historical subject that watches them and if we can consider this representation relevant to a historical understanding.